2007
DOI: 10.1097/00002800-200701000-00009
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Evaluation of a Family Nursing Intervention

Abstract: Congestive heart failure is a major source of anxiety for both patients and their family. This article presents the results of a qualitative case study aimed at evaluating family nursing interventions from the perspective of the family members and a clinical nurse specialist (CNS). A CNS applied a family nursing intervention program with 4 couples. Data were obtained through semistructured interviews preintervention and postintervention for the couples and postintervention for the CNS. The transcripts of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 17 publications
6
60
0
Order By: Relevance
“…The increased insight into CHF and its effect on the ill person provided the family members in the present study with a better understanding and tolerance in different situations for the person with CHF. This is in line with the findings by Duhamel and colleauges [20] where the spouses expressed that they became more understanding of the ill person. The acquired knowledge created security because family members were better prepared to handle different situations associated with CHF.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The increased insight into CHF and its effect on the ill person provided the family members in the present study with a better understanding and tolerance in different situations for the person with CHF. This is in line with the findings by Duhamel and colleauges [20] where the spouses expressed that they became more understanding of the ill person. The acquired knowledge created security because family members were better prepared to handle different situations associated with CHF.…”
Section: Discussionsupporting
confidence: 91%
“…[15,17,20,21] Our results also showed that the acquired knowledge was useful in daily life for both family members and the ill person. Duhamel and colleagues [20] also found that both the spouse and the ill person learned how to deal with the disease better. The increased insight into CHF and its effect on the ill person provided the family members in the present study with a better understanding and tolerance in different situations for the person with CHF.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations